Patients with advanced pancreatic and biliary cancer appear vulnerable to SARS-CoV-2 Omicron variant: An observational study during the COVID-19 outbreak in Shanghai - Han, Tao; Chen, Lujun; Gu, Jia; Wu, Shen; Maihemuti, Maiweilan; Yang, Jue; Wang, Hao; Wu, Jun; Zhang, Yue; Cong, Yun; Wang, Jiening; Chen, Tingsong (Frontiers in Oncology, 2023)
Background: The COVID-19 pandemic has been spreading rapidly across the globe. Cancer patients have a higher risk of severe infections and associated mortality than the general population. However, the lethal effect of Omicron Variant affection on Pancreatic & biliary cancer patients are still not clear. Herein, we designed an observation study to shed light on the influence of Omicron Variant on this so-called “King of Cancer”, to improve management in these patients with COVID-19 in the future. Methods: Omicron infected patients with advanced pancreatic & biliary cancer were enrolled from April 15 to May 31, 2022. Four groups were set in this study: Group 1, Omicron-infected cancer patients (N=4); Group 2, non-infected cancer patients (N=4); Group 3, infected non-cancer-afflicted subjects (N=4); Group 4, non-infected non-cancer-afflicted subjects (N=4). On Day 0, 7 and 14 after infection, the blood samples were dynamically collected from all subjects. The primary endpoints were disease severity and survival. Results: By the endpoints in this observational study, Patients No. 2, 3 and 4 died separately at Day 11, 25 and 13 after viral infection, all of whom were patients with advanced cancer, with the death rate up to 75%. Group 1 presented an overall T cell exhaustion status compared with other groups with obviously lower T cell populations and higher B cell% and CD4+T/CD8+T ratio (P<0.05). Time-course cytokine monitoring results showed that IL-1β was significantly decreased in Group 1 (P<0.05) and generally kept at a low level without obvious fluctuation. IL-6 was markedly increased in infected cancer patients (P<0.01), but remained a low level and had no apparent change during the whole infection process in non-cancer-afflicted subjects. Furthermore, several inflammatory parameter indexes indicated a tight association of Omicron infection with disease course and prognosis of Omicron-infected cancer patients. Conclusions: Advanced pancreatic & biliary cancer patients with Omicron infection are associated with severity and poor outcomes. More attentions, protective measures and routine healthcare services should be recommended to these vulnerable populations on clinical practice during the pandemic in the foreseeable future.